Obtenção de ésteres metílicos utilizando dolomita como catalisador heterogêneo na reação de transesterificação - Chiba, Marlene Leiko (2017)
Climate change and environmental awareness of society have favored research into environmentally sustainable products and processes. Biodiesel is a fuel derived from renewable sources, such as vegetable oils and animal fats, which can partially or completely replace petroleum diesel. Conventionally, biodiesel is produced by homogeneous alkaline transesterification reaction, but studies have been carried out for the use of heterogeneous catalysts, which have advantages such as the reduction of effluent residues and the possibility of reuse of the catalyst. Dolomite is a limestone, an abundant material in nature and low cost, with industrial application in several areas. Recently, dolomite has been studied for use as a heterogeneous catalyst in biodiesel production. In the present study, a dolomite from a region of Cachoeiro de Itapemirim - ES was investigated for use as a heterogeneous catalyst in biodiesel production. The calcination of this dolomite at 900 °C for 2 hours resulted in materials with important characteristics, which were investigated by chemical analysis, XRD, TGA / DTG and SEM. These qualities ensured good catalysis of the reaction of transesterification of cottonseed oil with methanol in amount of 2% or 3% by weight of catalyst. It was also possible to reuse them for two more cycles. From the reactions resulted products with high concentrations of methyl esters of approximately 98% FAME, with methyl linoleate and methyl palmitate being the most expressive esters, and it was not necessary to use water in the purifications and other process steps.